Peran Komunikasi Multimedia Dalam Industri Pariwisata Ekonomi Kreatif Pada Desa Wisata Puncak Aua Sarumpun - edlina, ria; Defhany; Fitri , Kintan Rahmi; Martin, Robi (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
This research aims to determine the role of multimedia communication in the creative economy tourism industry in the Puncak Aua Sarumpun tourist village. "Understanding the role of multimedia communication needs for tourism village actors can be seen from the expected goals and positioning, so that tourist villages must understand how multimedia works and this knowledge is an important basis for practitioners in managing the role of multimedia communication to be more effective for tourism village managers and the government in dealing with its development. The research uses a descriptive qualitative approach. Determining informants in this study used a purposive mechanism by determining informant criteria. The informants in this research were tourism village managers and the Tanah Datar district government. Data collection techniques through in-depth interviews, observation and documentation. Data analysis in this research uses Miles and Huberman analysis techniques, namely data codification, data presentation, and conclusion drawing/verification. The results of research on the role of multimedia communication in the creative economy tourism industry in the Puncak Aua Sarumpun tourist village, there is still a low understanding of tourism managers to be able to access promotional interaction media in marketing tourist attractions and in the policies regulated by managers and the government in developing the Aua Sarumpun tourist village. is still focused on implementing events and cultural promotion and has not touched on the development of tourist attractions more specifically so that in its implementation it has not yet shown significant progress in its development through the process of conveying messages which is carried out interactively by combining it digitally. The inhibiting factor in carrying out the role of multimedia communication in the creative economy tourism industry in the Puncak Aua Sarumpun tourist village is that it has not been carried out optimally, this can be seen in the information delivery system which is still not able to reach the wider community with cooperation between the community and the local government evenly and the manager's lack of knowledge regarding the importance of multimedia promotion in increasing the existence of Puncak Aua Sarumpun tourism